2011
DOI: 10.1037/a0022370
|View full text |Cite
|
Sign up to set email alerts
|

The effects of practice schedule and critical thinking prompts on learning and transfer of a complex judgment task.

Abstract: Many instructional strategies that appear to improve learners' performance during training may not realize adequate posttest performance or transfer to a job. The converse has been found to be true as well: Instructional strategies that appear to slow the learner's progress during training often lead to better posttraining or transfer performance. For example, many studies have shown beneficial effects of random over blocked practice on transfer of learning, even though blocked practice often leads to better p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 113 publications
(133 reference statements)
2
50
1
1
Order By: Relevance
“…A common finding in the contextual interference literature is that interleaved practice schedules facilitate long-term retention and performance on transfer tests, but lead to lower performance during the acquisition phase than blocked practice schedules (e.g., De Croock et al, 1998;Helsdingen et al, 2011;Lee & Simon, 2004;Shea & Morgan, 1979;Wulf & Shea, 2002). In our study, however, we found no difference across conditions in the performance during practice, as indicated by our analysis of the tutor log data, described above (see Fig.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…A common finding in the contextual interference literature is that interleaved practice schedules facilitate long-term retention and performance on transfer tests, but lead to lower performance during the acquisition phase than blocked practice schedules (e.g., De Croock et al, 1998;Helsdingen et al, 2011;Lee & Simon, 2004;Shea & Morgan, 1979;Wulf & Shea, 2002). In our study, however, we found no difference across conditions in the performance during practice, as indicated by our analysis of the tutor log data, described above (see Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Whether the notion that, in domains in which learning tasks vary across multiple dimensions (e.g., representations and task types), one should interleave learning tasks along the dimension with the greatest variability (i.e., in the present experiment task Table 6 Overview of study results on differences between conditions, obtained from HLM described in Equation (2) (De Croock et al, 1998;Helsdingen et al, 2011;van Merrienboer et al, 2002;Rohrer & Taylor, 2007;Taylor & Rohrer, 2010), but none of them have investigated whether the variability of the dimension on which learning tasks are interleaved matter. As argued, interleaving highly dissimilar learning tasks may decrease the likelihood that abstraction can occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleaved schedules, on the other hand, provide frequent opportunities to compare different graphical representations to one another (every time the student switches from one representation to the other), thus allowing students to make connections between different representations. Research shows that interleaved practice schedules lead to better long-term retention and transfer than blocked practice in a variety of domains including vocabulary learning (Bahrick et al 1993;Cepeda et al 2006), motor tasks (Hebert et al 1996;Immink and Wright 1998;Li and Wright 2000;Meiran 1996;Meiran et al 2000;Ollis et al 2005;Schmidt and Bjork 1992;Shea and Morgan 1979;Simon and Bjork 2001), algebra (Rohrer 2008;Rohrer and Taylor 2007;Rohrer 2010), troubleshooting (de Croock et al 1998;Van Merriënboer et al 2002), and decision-making tasks (Helsdingen et al 2011). However, interleaved practice schedules often result in lower performance during the acquisition phase (i.e., while students practice).…”
Section: Multiple Graphical Representations Of Fractionsmentioning
confidence: 99%
“…Analyzing student performance during the acquisition phase (i.e., while students learn) is particularly interesting when investigating the effects of practice schedules: a common finding is that interleaved practice schedules lead to better long-term retention and to better transfer than blocked schedules, but they often lead to worse performance during the acquisition phase (Battig 1972;de Croock et al 1998;Helsdingen et al 2011;Pashler et al 2007;Rohrer and Taylor 2007;Schmidt and Bjork 1992;Schneider 1985;Simon and Bjork 2001;Van Merriënboer et al 2002). Therefore, it is often believed that the advantage of interleaved practice over blocked practice is not apparent during the acquisition phase, but can only be detected with long-term retention tests and transfer tests administered after the acquisition phase.…”
Section: Bayesian Knowledge Tracing: Differences During the Acquisitimentioning
confidence: 99%